Pengaruh Kualitas Pelayanan Dan Persepsi Harga Pasca Pembelian Terhadap Kepuasan Pelanggan Pada Bengkel Resmi Suzuki Padjajaran Di Bogor - Yusup Sunandar; Hartanti Nugrahaningsih; Imam Sundarta (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
The aim of this research is to determine the effect of service quality and post-purchase price perceptions on customer satisfaction at the official Suzuki Padjadjaran repair shop in Bogor. The methods used are library research and field research using questionnaires. The research was conducted with customers who serviced their vehicles, namely a population of 400 customers, a sample of 200 customers. This research instrument is in the form of a questionnaire. The results of the research instrument test using multiple regression analysis tests, t tests, and f tests. The results of this research. The Service Quality Variable (X1) has a positive relationship with the Customer Satisfaction Variable (Y), which means that if there is an increase in Service Quality then Customer Satisfaction will also will experience an increase. The Price Perception variable (X2) has a positive relationship with the Customer Satisfaction variable (Y), which means that if there is an increase in Price Perception, Customer Satisfaction will also increase. The Customer Satisfaction variable (X1) and the Price Perception variable (X2) have a positive relationship with the Customer Satisfaction variable (Y), which means that if there is an increase in the independent variable, the dependent variable will also experience an increase